Malignant melanotic schwannoma of the bronchus. Issue 12 (December 1987) - Rowlands, D; Edwards, C; Collins, F
Abstract : A case of malignant melanotic schwannoma arising in the right upper lobe bronchus of a 27 year old man is presented. Tumours of this type most commonly occur in spinal nerve roots and are generally considered to be benign. The behaviour of those originating elsewhere is less predictable. As far as we are aware this is the first reported case affecting the respiratory tract.